MONTE CARLO SAMPLING TECHNIQUES FOR COMPUTATION OF MULTIDIMENSIONAL INTEGRALS RELATED TO MIGRATION: MONTE CARLO SAMPLING TECHNIQUES FOR COMPUTATION OF MULTIDIMENSIONAL INTEGRALS RELATED TO MIGRATION - Todorov, Venelin; Dzhurov, Valerij; Stanchev, Tosho; Tsvetkov, Iliyan; Dimitrov, Yuri (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
We study multidimensional integrals with applications to international migration forecasting. A comprehensive experimental study based on Latin Hypercube and Importance Sampling and Fibonacci based lattice rule has been done. This is the first time such a comparison has been made. The numerical tests show that the stochastic algorithms under consideration are efficient tool for computing multidimensional integrals. It is important in order to obtain a more accurate and reliable interpretation of the results which is a foundation in international migration forecasting.